Improvement of Clinical and Experimental Characteristics and Treatment of Acute Rhinosinusitis in Patients (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Among the pathologies of the upper respiratory tract that significantly worsened the patient's health and quality of life, inflammatory diseases of the nasal cavity and paranasalRsinuses occupy one of the leading places. One of the leaders here is rhinosinusitis, primarily because of the widespread prevalence of this disease and its growth.The data on its actual epidemiology are extremely diverse: There are also inconsistencies in the criteria for making a diagnosis (clinical symptoms, results of an X-rayor diagnostic puncture of the paranasal sinuses (ONP), and low patient referral for professional help for mild forms of the disease, and the fact that rhinosinusitis often develops against the background of ARVI.